Top-down strategy synthesis of fluorinated graphdiyne for lithium ion battery. Issue 54 (2nd October 2019) - Kang, Huifang; Chen, Yue; Xu, Lanqing; Lin, Yuda; Feng, Qian; Yao, Hurong; Zheng, Yongping
Abstract : Fluorine doped graphdiyne was synthesized by exposure to XeF2 under mild temperature. Owing to the enhanced conductivity and enhanced mechanical properties, the electrochemical performances are significantly improved. Abstract : As a novel carbon allotrope, graphdiyne exhibits excellent electrochemical properties such as high specific capacities, outstanding rate performances, and long cycle lives. These properties are attributed to its sp- and sp 2 -hybridized bonding and a natural large pore structure. Doping with light elements is a facile way to improve the electrochemical performance of graphdiyne. Herein, we report the preparation of fluorine-doped graphdiyne by exposure to XeF2 under a mild temperature. Compared to pristine graphdiyne, the capacities are doubled. We obtained reversible capacities of fluorinated graphdiyne up to 1080 mA h g −1 after 600 cycles at a current density of 500 mA g −1 . At a higher current density of 1000 mA g −1, it still retained a high specific capacity of 693 mA h g −1 after 1000 cycles. Using in situ quantitative nanomechanical probe atomic force microscopy, we further analyzed the surface morphologies and elastic modulus to understand the mechanism of the electrochemical improvement. The fluorinated graphdiyne elastic modulus is doubled in contrast to pristine graphdiyne. The performance improvements are attributed to the improvement in conductivity and enhancement of the mechanical properties.